2014
DOI: 10.5301/ijao.5000309
|View full text |Cite
|
Sign up to set email alerts
|

First Impressions of Cardiovascular Calcification Treatment in Hemodialysis Patients with a New Dialysis Fluid Containing Sodium Thiosulphate (STS)

Abstract: The first results are hopeful, but the number of the patients was small, so we are enlarging the enrollment in the expectation of corroborating our results soon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 19 publications
1
15
1
Order By: Relevance
“…In addition to the two studies cited in the paper, in which, respectively, eighty-six patients were treated for 4 months and twenty-two patients for 5 months, both reporting positive results without relevant side effects, we were able to retrieve three further studies that, albeit with different deigns, reported, once more in the absence of relevant side effects, a positive effect on arterial stiffness (in twenty-four patients randomised for receiving treatment for 5 months [4]), leg pain related with vascular calcifications (18 heavily calcified patients, treated for 6 months [5]), and coronary artery calcifications (17 patients treated for 3 months [6]). In one further study, in which sodium thiosulphate was added to the dialysis fluid, a "positive impression" was reported in six cases [7]. Significantly, the data are in keeping with the few, albeit convincing, animal and in vitro studies published.…”
supporting
confidence: 66%
“…In addition to the two studies cited in the paper, in which, respectively, eighty-six patients were treated for 4 months and twenty-two patients for 5 months, both reporting positive results without relevant side effects, we were able to retrieve three further studies that, albeit with different deigns, reported, once more in the absence of relevant side effects, a positive effect on arterial stiffness (in twenty-four patients randomised for receiving treatment for 5 months [4]), leg pain related with vascular calcifications (18 heavily calcified patients, treated for 6 months [5]), and coronary artery calcifications (17 patients treated for 3 months [6]). In one further study, in which sodium thiosulphate was added to the dialysis fluid, a "positive impression" was reported in six cases [7]. Significantly, the data are in keeping with the few, albeit convincing, animal and in vitro studies published.…”
supporting
confidence: 66%
“…A total of 83 papers were screened independently by TP and DH. Forty‐five studies including 358 patients met the inclusion criteria . These included 36 case reports and nine multi‐case reports.…”
Section: Resultsmentioning
confidence: 99%
“…Chronic EG exposure leads to hyperoxaluria, renal crystal deposition, oxidative stress and impaired kidney function [ 18 22 ]. Given the increasing use of STS in humans [ 23 25 ] and its reported beneficial effects in calcifying/crystallizing conditions [ 11 ], we aimed to investigate the effect of STS on EG-induced crystal burden and renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%